+0  
 
0
329
2
avatar

What is -6t x 4m x (-m)?

Guest Aug 10, 2017
 #1
avatar+349 
0

I'm assuming you mean simplify? I'm gonna do that.

 

\(-6t*4m*(-m)\)

-m can be expressed as -1*m, and -6t can be expressed as -1*6t: \(-1*-1*6t*4m*m\)

-1 * -1 = 1: \(1*6t*4m*m=6t*4m*m\)

m * m = m2\(6t*4m*m=6t*4*(m*m)=6t*4*m^2\)

Factor out 2: \(2(3t*2m^2)\)

 

The simplest form of the expression is \((2(3t*2m^2))...or...(6t*4m^2)\)

Mathhemathh  Aug 10, 2017
 #2
avatar+7002 
0

It's not the simplest form ._.

\(-6t \cdot 4m \cdot (-m)\\ =(-6\cdot 4)\cdot(t\cdot m\cdot(-m))\\ =-24(-tm^2)\\ =24tm^2\)

Simplest form should be 24tm^2...

MaxWong  Aug 11, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.